KOMUNIKASI TRADISI MANGAIN MARGA DALAM PERNIKAHAN BATAK TAPANULI SELATAN DI PEKANBARU - Tondi Hariara Pane; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Communication is something that cannot be separated from human life in their daily lives with other people around them. Communication is also very necessary in a customary tradition of mangain marga, while the traditional tradition of mangain marga is carried out by the Batak tribe of South Tapanuli. The purpose of this research is to explain how the stages of traditional communication in mangain marga in the South Tapanuli Batak wedding in Pekanbaru and how the meaning of tradition in the mangain marga in the South Tapanuli Batak wedding in Pekanbaru.This research was conducted on Jalan Sigunggung at the house of the traditional leader of the Batak Tapanuli Selatan Pekanbaru and this research was also carried out with the South Tapanuli Batak tribe who live in Pekanbaru. This study uses a qualitative descriptive research method that explains and interprets existing data. The informants in this study were the traditional and tribal leaders of the Batak South Tapanuli Pekanbaru by using a purposiv technique. Data collection techniques using observation, interviews, and documentation.The results of this study indicate the stages of traditional communication in the mangain marga in the Batak South Tapanuly wedding in Pekanbaru well, although sometimes there are problems, they can be resolved properly by both parties and the meaning of the mangain marga tradition in the South Tapanuli Batak wedding. in Pekanbaru also went well and was accepted by both parties. Keywords: Tradition communication, mangain marga and stages of mangain marga, research method.